2018
DOI: 10.7196/ajhpe.2018.v10i1.981
|View full text |Cite
|
Sign up to set email alerts
|

A survey of radiation safety training among South African interventionalists

Abstract: Interventionalists are highly specialised doctors who undergo rigorous training. The use of ionising radiation is an integral part of their medical practice and potentially poses major occupational health risks, such as skin damage, genetic and chromosomal aberrations, carcinomas and cataract formation. [1] The use of this modality for diagnostic, treatment and interventional procedures has increased substantially, posing greater occupational risks. [2] In medicine, occupational radiation protection is challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Another evidence for progress in awareness is the increased research by scientists and students. Over the last ten years, several African undergraduate, postgraduate students and doctoral students have done research and published dissertations and theses on different aspects radiation safety [ 39 , 40 ].…”
Section: Impact Of Covid-19 On Quality and Safety For Imaging In Africamentioning
confidence: 99%
“…Another evidence for progress in awareness is the increased research by scientists and students. Over the last ten years, several African undergraduate, postgraduate students and doctoral students have done research and published dissertations and theses on different aspects radiation safety [ 39 , 40 ].…”
Section: Impact Of Covid-19 On Quality and Safety For Imaging In Africamentioning
confidence: 99%
“…7 A South African study explained that radiation protection practices were lacking because radiation is invisible, and effects possibly occurring later in life. 21 Similarly, an Iranian study showed that the majority of radiographers had a weak or moderate performance of radiation protection. 22 Studies in Northern Nigerian 23 and California 24 also indicated poor radiation protection practices.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a retrospective evaluation of 100 pre‐processed neonatal chest X‐rays revealed that 77% were not collimated optimally 7 . A South African study explained that radiation protection practices were lacking because radiation is invisible, and effects possibly occurring later in life 21 . Similarly, an Iranian study showed that the majority of radiographers had a weak or moderate performance of radiation protection 22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations